Optimization of Hybrid Power Plant System to Increase Reliability by Maximizing Renewable Energy (Case Study: Semau Island) - Utami, Ananda Rizky; Mulyana, Iwa Garniwa (DPTE FT UNY, 2024)
Semau Island is one of the islands in the 3T region. Semau Island's electricity system is supplied by 5 diesel engines, Solar Power Plant, and battery storage, with a renewable energy mix that reaches 13%. This is not in accordance with the target renewable energy mix in Indonesia in 2025 which is 23%. The generation operation pattern applied on Semau Island experiences blackouts due to intermittent conditions when the Solar Power Plant fully supplies the load during the day and the battery is unable to back up. So, to mitigate the intermittency nature of the Solar Power Plant while still increasing the penetration of renewable energy, it is necessary to optimize the integrated generation operation pattern between the Solar Power Plant, the diesel engine and the battery storage. In this research, optimization is carried out using HOMER software. The HOMER application uses a derivative-free algorithm in the HOMER Optimizer feature to find the cheapest system. The optimization results in the existing scenario found that the use of 2 diesel engines, namely DG Mdec, DG Adec in base load operations and a combination of PV and batteries can optimize the operating pattern with NPC costs of 9762426, O&M costs of 583589 and LCOE value of 0.1999/kWh.